Association of glucose homeostasis measures with heart rate variability among Hispanic/Latino adults without diabetes: the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). Issue 1 (December 2016) - Meyer, Michelle; Gotman, Nathan; Soliman, Elsayed; Whitsel, Eric; Arens, Raanan; Cai, Jianwen; Daviglus, Martha; Denes, Pablo; González, Hector; Moreiras, Juan; Talavera, Gregory; Heiss, Gerardo
Abstract Background Reduced heart rate variability (HRV), a measure of cardiac autonomic function, is associated with an increased risk of cardiovascular disease (CVD) and mortality. Glucose homeostasis measures are associated with reduced cardiac autonomic function among those with diabetes, but inconsistent associations have been reported among those without diabetes. This study aimed to examine the association of glucose homeostasis measures with cardiac autonomic function among diverse Hispanic/Latino adults without diabetes. Methods The Hispanic community Health Study/Study of Latinos (HCHS/SOL; 2008–2011) used two-stage area probability sampling of households to enroll 16, 415 self-identified Hispanics/Latinos aged 18–74 years from four USA communities. Resting, standard 12-lead electrocardiogram recordings were used to estimate the following ultrashort-term measures of HRV: RR interval (RR), standard deviation of all normal to normal RR (SDNN) and root mean square of successive differences in RR intervals (RMSSD). Multivariable regression analysis was used to estimate associations between glucose homeostasis measures with HRV using data from 11, 994 adults without diabetes (mean age 39 years; 52 % women). Results Higher fasting glucose was associated with lower RR, SDNN, and RMSSD. Fasting insulin and the homeostasis model assessment of insulin resistance was negatively associated with RR, SDNN, and RMSSD, and the association was stronger among men compared with women. RMSSD was, on average, 26 % lower in men with higher fasting insulin and 29 % lower in men with lower insulin resistance; for women, the corresponding estimates were smaller at 4 and 9 %, respectively. Higher glycated hemoglobin was associated with lower RR, SDNN, and RMSSD in those with abdominal adiposity, defined by sex-specific cut-points for waist circumference, after adjusting for demographics and medication use. There were no associations between glycated hemoglobin and HRV measures among those without abdominal adiposity. Conclusions Impairment in glucose homeostasis was associated with lower HRV in Hispanic/Latino adults without diabetes, most prominently in men and individuals with abdominal adiposity. These results suggest that reduced cardiac autonomic function is associated with metabolic impairments before onset of overt diabetes in certain subgroups, offering clues for the pathophysiologic processes involved as well as opportunity for identification of those at high risk before autonomic control is manifestly impaired.